Identification of Radial Glia Progenitors in the Developing and Adult Retina of Sharks - Sánchez-Farías, Nuria; Candal, Eva (Frontiers in Neuroanatomy, 2016)
Neural stem cells give rise to transient progenitors termed neuroepithelial cells (NECs) and radial glial cells (RGCs). RGCs represent the major source of neurons, glia and adult stem cells in several regions of the central nervous system (CNS). RGCs are mostly transient in mammals, but they are widely maintained in the adult CNS of fishes, where they continue to be morphologically similar to RGCs in the mammalian brain and fulfill similar roles as progenitors and guide for migrating neurons. The retina of fishes offers an exceptional model to approach the study of adult neurogenesis because of the presence of constitutive proliferation from the ciliary marginal zone, containing NECs, and from adult glial cells with radial morphology (the Müller glia). However, the cellular hierarchies and precise contribution of different types of progenitors to adult neurogenesis remain unsolved. We have analyzed the transition from NECs to RGCs and RGC differentiation in the retina of the cartilaginous fish Scyliorhinus canicula, which offers a particularly good spatial and temporal frame to investigate this process. We have characterized progenitor and adult RGCs by immunohistochemical detection of glial markers as GFAP and GS. We have compared the emergence and localization of glial markers with that of PCNA (a proliferation maker) and DCX (which increases at early stages of neuronal differentiation). During retinal development, GFAP-immunoreactive NECs located in the most peripheral ciliary marginal zone codistribute with DCX-immunonegative cells. GFAP-immunoreactive RGCs and Müller cells are located in successive more central parts of the retina and codistribute with DCX- and DCX/GS-immunoreactive cells, respectively. The same types of progenitors are found in juveniles, suggesting that the contribution of the ciliary marginal zone to adult neurogenesis implies a transition through the radial glial state.